Clinical and cost outcomes of pre-emptive plerixafor administration in patients with multiple myeloma undergoing stem cell mobilization. (October 2019) - Andritsos, Leslie A.; Huang, Ying; Abraham, Ivo; Huff, Keith; Scrape, Scott R.; Fan, Tao; Alkhatib, Nimer; Hofmeister, Craig C.; Drea, Edward; McBride, Ali
Highlights: Plerixafor is approved for CD34+ cell mobilization, but cost considerations limit its routine use. Our center needed to improve collection efficiency to enhance apheresis resource utilization. Plerixafor was administered to all myeloma patients undergoing mobilization. This change resulted in improved collection efficiency without increasing overall costs. Abstract: Purpose: The stem cell mobilization agent plerixafor significantly improves CD34 + stem cell procurement in patients with multiple myeloma undergoing autologous stem cell transplant. We compared mobilization success rates and costs of two regimens of plerixafor administration: pre-emptive (P-PL, initiated the evening prior to the first day of stem cell collection) and standard (S-PL, initiated the evening prior to the second day of stem cell collection in the event of inadequate collection on the first day). Methods: Patients with multiple myeloma undergoing mobilization were categorized as either P-PL or S-PL. Stem cell collection success was evaluated using logistic regression models. Associated costs were aggregated in terms of average collections per patient in each mobilization option (patient level), and escalated to a panel of 5000 patients (population level). Results: 299 patients were evaluable; 241 received P-PL and 58 received S-PL. Patients receiving P-PL had higher median CD34 + count pre-collection and higher median total CD34 + cell harvest on the first collection (6.75 × 10 6 /kg for P-PL, 1.96 × 10 6 /kg for S-PL; P< 0.01). In multivariable analyses, P-PL remained significantly associated with the ability to collect ≥2 × 10 6 /kg CD34 + on the first day (OR = 4.05, 95% CI, 1.19–13.83, P = 0.03) and ≥5 × 10 6 /kg CD34 + in total (OR = 3.09, 95% CI, 1.04–9.23, P = 0.04). P-PL saved 11, 248 (46%) per patient compared with S-PL. Conclusion: P-PL significantly enhanced collection efficiency, with most patients completing collection in 1 day, resulting in substantial cost savings.